Pengaruh Good Corporate Governance, Leverage, Kebijakan Dividen Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia Periode 2017 s.d. 2019) - Izhatul Ulia; Ronny Malavia Mardani; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this research is to find out how the influence of Good Corporate Governance, Leverage and Dividend Policy on Earnings Management. The population in this study consisted of 30 Manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Purposive sampling method with a sample of 11 companies from 30 food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The results of the study partially show that: 1) There is no effect of managerial ownership on earnings management 2) There is an effect of leverage on earnings management 3) There is an effect of dividend policy on earnings management.  Keywords: Good Corporate Governance, Leverage, Dividend Policy and Profit Management